Organic synthesis using transition metals - Bates, Roderick (Wiley, 2012)
"Organic Synthesis Using Transition Metals, 2nd Edition considers the ways in which transition metals, as catalysts and reagents, can be used in organic synthesis. It concentrates on the bond-forming reactions that set transition metal chemistry apart from "classical" organic chemistry"--